THE MECHANISM OF FINANCING THE GREEN ECONOMY IN UZBEKISTAN - Rajabov Saddambek Utkir ogli (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the article is to further accelerate the financing of the "green economy" in Uzbekistan and increase its use, mainly to study the conditions and actions for the use of renewable energy sources, to find opportunities to accelerate this process. The article discusses the institutional framework for financing the "green economy", the main directions of economic development. Suggestions are made for the widespread introduction of renewable energy sources and energy efficiency in housing and communal services, social facilities and other areas.